2017
DOI: 10.1039/c7ra04554a
|View full text |Cite
|
Sign up to set email alerts
|

The complete utilization of rice husk for production of synthesis gas

Abstract: Rice husk was completely used for synthesis gas production. The pyrolysis volatiles (gas and bio-oil) of rice husk were used as raw materials to produce synthesis gas and the bio-char from the rice husk pyrolysis was used as the catalyst for catalytic reforming of pyrolysis volatiles of rice husk. We investigated the role of catalysts in gas and bio-oil catalytic reformation under different reaction conditions and the interaction between gas and bio-oil. The results indicated that 0.1Ni-0.1Co/RHPC (rice husk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The concentration of gas is almost the same as the mold gas. The real pyrolysis volatiles catalytic tests were carried out on a continuous pyrolysis reactor which was used in our previous research . The results are shown in Figure (c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentration of gas is almost the same as the mold gas. The real pyrolysis volatiles catalytic tests were carried out on a continuous pyrolysis reactor which was used in our previous research . The results are shown in Figure (c).…”
Section: Resultsmentioning
confidence: 99%
“…The gas products were analyzed with GC. Catalytic tests of real pyrolysis volatiles were carried out in a continuous pyrolysis reactor which was used in our previous research, 4 and it combined rice husk pyrolysis and catalytic reforming of pyrolysis volatiles. Both the pyrolysis and catalytic reforming temperatures are 500 °C.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, in the field of bioenergy, a common procedure to obtain energy from rice husks is using thermochemical processes as direct combustion, pyrolysis, gasification and liquefaction [49]. Various authors [50][51][52][53] identified pyrolysis as the most promising and effective method to obtain energy and create products like bio-char, bio-oil and pyrolysis gas. Manatura et al [54] presented an exergy analysis of combined torrefaction and gasification process on rice husks pellets.…”
Section: Availability Of Paddy Rice Residual Biomass and Possibilities Of Energy Usementioning
confidence: 99%